Effect of using Nearshore breakwaters on shoreline response south of lattakia city - Sheha, Mais (Latakia University Journal -Engineering Sciences Series, 2025)
The problem of beach erosion is one of the serious issues facing coastal areas, especially if those areas are economically and touristically productive. .Alramel alganobi beach is experiencing a noticeable retreat in the shoreline, which necessitates protecting the area using one or more protective measures. Nearshore breakwaters are a means to reduce erosion and increase the stability of the shoreline. Therefore, two different scenarios for the placement of breakwaters were proposed using the JMC computational method. This article aims to analyze the effectiveness of breakwaters and their impact on the shape of the shoreline using the GENCADE numerical model, with a precise calibration of the model to ensure reliable results. The results showed that the breakwaters have had a limited success in reducing erosion due to the absence of an external sediment supply, which negatively affected their effectiveness. Thus, they do not represent a sufficient solution on their own unless additional sand is introduced to the project area (artificial nourishment). The research recommends that when planning coastal management projects, multiple strategies should be integrated to achieve effective results.